Effect of iron on biological clogging in porous media: Implications for managed aquifer recharge. Issue 3 (9th March 2023) - Cui, Ruijuan; Page, Declan; Du, Xinqiang; Zhang, Hexuan; Ye, Xueyan
Abstract: Managed aquifer recharge (MAR) is increasingly being adopted to improve water security internationally. However, clogging during MAR remains one of the greatest challenges for sustainable operations. This study examines the effects of iron on biological clogging processes using column experiments and suggests management options. The results indicated that the presence of iron limits the transport of bacteria through the column, and that concentrations <10 mg/L are correlated with increased bacterial growth. Conversely, the increased viscosity of biofilm subsequently limits the transport of iron through the column. Fourier transform infrared spectroscopy and x‐ray photoelectron spectroscopy indicated that large iron‐ Pseudomonas sp. flocs formed which occupied the sand pore spaces. The effect of iron induced chemical clogging was most notable in the initial stage of the experiment while bio‐clogging dominated later. There are many recommended values of iron concentration in water recharge, most of them are advised from the point of pollution perspective. Based on these laboratory results, iron concentrations in recharge water for MAR should be <0.3 mg/L to mitigate clogging effects. Furthermore, using non‐corrodible materials for bore screen and pumps, and avoiding external oxidant inputs should be considered to prevent iron related chemical and biological clogging. Abstract : The combined biological‐chemical clogging was closely related to the iron concentration. An iron water quality target in recharge water for MAR should be <0.3 mg/L to mitigate clogging effects.